Unveiling the “hidden quality” of the walnut pellicle: a precious source of bioactive lipids - Abbattista, Ramona; Feinberg, Noah G.; Snodgrass, Isabel F.; Newman, John W.; Dandekar, Abhaya M. (Frontiers in Plant Science, 2024)
Tree nut consumption has been widely associated with various health benefits, with walnuts, in particular, being linked with improved cardiovascular and neurological health. These benefits have been attributed to walnuts' vast array of phenolic antioxidants and abundant polyunsaturated fatty acids. However, recent studies have revealed unexpected clinical outcomes related to walnut consumption, which cannot be explained simply with the aforementioned molecular hallmarks. An untargeted metabolomics profiling of the walnut pellicle (seed coat) revealed a myriad of unusual lipids, including oxylipins and endocannabinoids, that have known potent bioactivities as mammalian signaling molecules and homeostatic regulators. The discovery of these compounds in the pellicle, which likely enhances the seeds' defenses due to their antimicrobial properties, represents a potential explanation for these unexpected clinical outcomes of walnut consumption. Given the potential value of this tissue and its "bioactive" lipid fraction for human health, we sought to quantify the amounts of these compounds in waste by-products of mechanized walnut processing in California. An impressive repertoire of these compounds was revealed, and in notably significant concentrations, making this low-value agriculture waste a promising candidate for valorization and translation into high-value, health-promoting products. This "hidden quality" of the walnut pellicle may encourage further consumption of walnuts, and walnut industries may benefit from a revaluation of abundant pellicleenriched waste streams, leading to increased sustainability and profitability through waste upcycling.1 Introduction Consumer demand for tree nuts, such as almonds, pistachios, and walnuts, continues to increase globally. Based on available data from the USDA Economic Research Service, the per capita consumption of shelled tree nuts has increased from 3.8 pounds in 2010 to almost 6 pounds in 2021. Shelled tree nuts, which consist of only the edible portion of the nut, are popular among consumers for various reasons. They have cultural significance, can be utilized in many diverse culinary applications, are a tasty, nutritional, and convenient snack, and are increasingly recognized for their health benefits. Government health agencies worldwide encourage the consumption of tree nuts, describing them as nutrient-dense foods that provide essential dietary components and bioactive compounds (U.S.